The Asymptotes of Power - Shimshon Bichler; Jonathan Nitzan (Real-World Economics Review, 2012)
This is the latest in a series of articles we have been writing on the current crisis. The purpose of our previous papers was to characterize the crisis. We claimed that it was a 'systemic crisis', and that capitalists were gripped by 'systemic fear'. In this article, we seek to explain why. The problem that capitalists face today, we argue, is not that their power has withered, but, on the contrary, that their power has increased. Indeed, not only has their power increased, it has increased by so much that it might be approaching its asymptote. And since capitalists look not backward to the past but forward to the future, they have good reason to fear that, from now on, the most likely trajectory of this power will be not up, but down. The paper begins by setting up our general framework and key concepts. It continues with a step-by-step deconstruction of key power processes in the United States, attempting to assess how close these processes are to their asymptotes. And it concludes with brief observations about what may lie ahead.
Keywords: 330; capitalization; distribution; power; systemic crisis; United States